2011
DOI: 10.5213/inj.2011.15.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Detrusor Overactivity in Patients with Overactive Bladder Symptoms

Abstract: PurposeTo evaluate the relationship between urodynamic detrusor overactivity (DO) and overactive bladder (OAB) symptoms in men and women.MethodsWe reviewed the records of adult males and females who attended a tertiary referral center for urodynamic evaluation of OAB syndrome symptoms with the presence or absence of DO. DO was calculated for symptoms alone or in combination.ResultsThe overall incidence of DO was 76.1% and 58.7% in male and female OAB patients, respectively. Of men 63% and 61% of women with urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…Furthermore, we pooled the data of comparison between OAB‐wet and OAB‐dry patients, it showed OAB‐wet group had a higher urinary NGF/Cr level than OAB‐dry group. Because OAB‐wet patients are more related to detrusor overactivity (DO), it is postulated that OAB patients with DO could have higher urinary levels of NGF/Cr than those without DO. Above‐mentioned results suggested that NGF might have a potential to be a biomarker for diagnosis and evaluation of OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we pooled the data of comparison between OAB‐wet and OAB‐dry patients, it showed OAB‐wet group had a higher urinary NGF/Cr level than OAB‐dry group. Because OAB‐wet patients are more related to detrusor overactivity (DO), it is postulated that OAB patients with DO could have higher urinary levels of NGF/Cr than those without DO. Above‐mentioned results suggested that NGF might have a potential to be a biomarker for diagnosis and evaluation of OAB.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the use of UDS prior to surgery correlates with treatment outcome has long been controversial. In addition, up to 40% of women with clinical symptoms of OAB and UUI will not demonstrate overactivity on UDS . A Cochrane review from 2002 studied the impact of UDS and found insufficient data to support or refute the importance of urodynamics testing prior to surgical intervention .…”
Section: Discussionmentioning
confidence: 99%
“…There was a better correlation in results between OAB symptoms and the urodynamic diagnosis of DO in men than in women, more so in OAB wet than in OAB dry. 17 Pharmacotherapies that target the prostate often fail to alleviate OAB symptoms, and may not be the most appropriate therapy for men with storage LUTS. Multiple studies have suggested that antimuscarinics alone or in combination with alpha1-receptor antagonists improve OAB symptoms in men with and without BOO.…”
Section: Male Luts and Oab E Backgroundmentioning
confidence: 99%